Social policies and ethnic conflict in China : lessons from Xinjiang - Zhang, Shaoying; McGhee, Derek; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study addresses how China's policy response to problems in Xinjiang is interpreted and implemented by officials, who are both governing agents and governed subjects by interviewing Chinese officials working in both Central government and Local governments.
Keywords: Science